2020
DOI: 10.1097/pas.0000000000001461
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Carcinomas with a “Serous” Component in Young Women Are Enriched for DNA Mismatch Repair Deficiency, Lynch Syndrome, and POLE Exonuclease Domain Mutations

Abstract: Endometrial carcinoma (EC), as described by Bokhman, has historically been classified as Type I (low-grade, hormone-dependant, young patients, good prognosis) or Type II (high-grade, hormone-independent, older patients, poor prognosis). This classification is no longer pragmatic, however, as EC is a much more heterogeneous disease. Four molecular subtypes of EC were identified by The Cancer Genome Atlas (TCGA), and subsequent studies have demonstrated its utility in predicting prognosis. While endometrial sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
6
37
0
Order By: Relevance
“…Indeed, the favorable prognostic value of the POLEmut group appears not to significantly change when normalized for possible confounding factors [ 13 ]. The excellent prognosis of the POLEmut group is maintained across the several histotypes, justifying the guidance of the ESGO/ESTRO/ESP guidelines [ 12 , 23 , 33 , 34 , 35 , 43 , 44 , 52 , 63 , 64 ]. On the other hand, the prognosis of the NSMP group appears heavily affected by tumor grade and histotype.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Indeed, the favorable prognostic value of the POLEmut group appears not to significantly change when normalized for possible confounding factors [ 13 ]. The excellent prognosis of the POLEmut group is maintained across the several histotypes, justifying the guidance of the ESGO/ESTRO/ESP guidelines [ 12 , 23 , 33 , 34 , 35 , 43 , 44 , 52 , 63 , 64 ]. On the other hand, the prognosis of the NSMP group appears heavily affected by tumor grade and histotype.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, even in the presence of morphologically unequivocal SC, applying the TCGA classification appears crucial to avoid severe overtreatment of patients. POLEmut and MMRd cases with serous features indeed show a prognosis comparable to that of their EEC counterpart, supporting the need for a similar management [ 34 , 35 ].…”
Section: Serous Carcinoma (Sec)mentioning
confidence: 85%
See 2 more Smart Citations
“…Atypical hyperplasia is associated with unopposed estrogenic stimulation of the endometrium and acquisition of mutations in PTEN , KRAS , PIK3CA , CTNNB1 , and/or ARID1A [57]. EAH/EIN is the precursor lesion of almost all endometrioid carcinomas and a subset of serous carcinomas [58]. The mutational profile of EAH/EIN and the concurrent EC is highly concordant [18,59–62] in the majority of cases; however, Li et al showed that, in 5 out of 30 EAH/EIC cases with concurrent EEC, the EAH/EIC and EC shared less than 5% of the mutations identified, indicating clonality but with a high degree of divergence [62].…”
Section: Precursors Of Endometrial Carcinomamentioning
confidence: 99%